PENGARUH CITRA MEREK TERHADAP LOYALITAS PELANGGAN DENGAN KEPERCAYAAN MEREK SEBAGAI VARIABEL MEDIASI (Studi Pada PT. Telkomsel Di Kota Makassar) - Muhammad Vicky Afrezkia Saleh; Anwar, Anwar; Nurul Fadilah Aswar; Chalid Imran Musa; Isma Azis Riu (Bajang Institute, 2025)
This study examines the effect of brand image on customer loyalty with brand trust as a mediating variable among PT. Telkomsel customers in Makassar City. Employing a quantitative causal design, the research utilized non-probability purposive sampling to select 117 respondents from an unknown population of PT. Telkomsel customers in Makassar City. Data collection was performed through questionnaires, and analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) version 4.0. Findings revealed four key results: (1) Brand Image positively and significantly influences Customer Loyalty, (2) Brand Image positively and significantly affects Brand Trust, (3) Brand Trust positively and significantly impacts Customer Loyalty, and (4) Brand Trust partially mediates the relationship between Brand Image and Customer Loyalty at PT. Telkomsel in Makassar City